Evaluation of the taxonomic status of the genus Aliella (Compositae, Gnaphalieae): a recircumscription of the genus Phagnalon - Montes-Moreno, Noemí; Garcia-Jacas, Núria; Benedí, Carles; Sáez, Llorenç (Phytotaxa, 2013)
A taxonomic evaluation of the genus Aliella, endemic to the Moroccan Atlas Mountains, is presented. We evaluate the taxonomic status of Aliella using a morphologic and molecular approach. Firstly, we discuss the variability and usefulness of its morphological diagnostic characters. Secondly, we analyse nuclear ETS and ITS, and chloroplast ycf3-trnS and trnT-trnL spacers. Phylogenetic analyses of the nrDNA and cpDNA spacers suggest the paraphyly of Aliella and Phagnalon. Two species of Aliella, A. ballii and A. embergeri, form a strongly supported clade. In contrast, relationships of A. platyphylla to A. ballii and A. embergeri are only weakly supported, and A. iminouakensis do not form a group with the other species and shows two different haplotypes. The morphological and diagnostic characters of Aliella are described and compared with an extensive sampling of the closely related genus Phagnalon. Our results strongly suggest that Aliella should be merged into Phagnalon. For each accepted taxon, taxonomical, chorological, and ecological data are provided. Six taxa are recognized, three species and three subspecies. Three lectotypifications of specific names and three new combinations are proposed. New descriptions and distribution maps of the recognized taxa are given.